(untitled) (Research, Society and Development, 2023)
Traditionally, structural analysis is based on the hypothesis that supports are indeslocable due to simplicity. However, the conventional design in which settlements of foundation elements are disregarded can lead to physical results that are incompatible with reality. This work aims to analyze the influence of the consideration of soil-structure interaction (SSI) on the responses of steel structural elements obtained by a static second order analysis. Furthermore, it is evaluated the responses obtained by different types of procedures for the consideration of soil stiffness in the structural analysis. Solid elements considering linearly elastic material parameters and spring elements based on the Winkler theory are employed. The analyses were performed with the commercial software SAP2000. Plane steel frames models were analyzed, either considering conventional supports or taking into account the soil-structure interaction. Shallow footing foundations are considered. Three frames with the same characteristics, but with a different number of floors were analyzed, showing the influence of the height increase and the building stiffness on the SSI results. It has been shown that the consideration of the effects of soil-structure interaction on structural analysis of buildings can have a significant influence on the stress distribution, displacements and structural behavior. In addition, it is concluded that the structural capacity of steel frames can be affected by the type of support adopted and by changes on the way the model considers soil deformation.